Pengaruh Variasi Jenis dan Ukuran Limbah Organik Terhadap Kadar Air Kompos Blok dan Pertumbuhan Tanaman Cabai - Novita, Elida; Andriyani, Idah; Romadona, Zakina; Pradana, Hendra Andiananta (Universitas Diponegoro, 2020)
Organic waste is potential as a compost material. It was supported by the amount of nutrient content. The compost block is a technology for utilizing organic material as a plant nursery. The research objective was to examine the variants of type and size of organic matter effect on the water content in compost blocks and vegetative growth of chili plants. The materials type of compost block were coffee pulp, tobacco petiole, and rice husks. Size variations in compost block were 10, 40 and 80 mesh. Experimental design on the types and sizes of organic materials using a Completely Randomized Design. The experimental results show that the highest value of water content in compost block with the watering of the same volume amount 51.22 mL of water is coffee pulp material with a range value of 40 - 50%. Coffee pulp and rice husk as compost block material influenced the vegetative growth of chili plants. The statistical tests that show a significant effect on the type and size of organic waste material on the chili plant growth i.e height and leaf area plants. The results become a consideration for variation type and size of organic waste choice for compost block materials.